ENERGY BALANCE IN FOREST, NATURAL FIELD AND AGRICULTURAL AREA IN THE MUNICIPALITY OF HUMAITÁ-AM - Lobato, Kim Besinge Miranda; Querino, Carlos Alexandre Santos; dos Santos, Luiz Octavio Fabricio; Querino, Juliane Kayse Albuquerque da Silva; dos Santos, Rosa Maria Nascimento (Ra’e Ga: o Espaço Geográfico em Análise, 2024)
The climatic consequences of changes in forest areas can be assessed through the analysis of the Surface Energy Balance, through either in situ measurements or remote data modeling, such as those carried out by SEBAL. Thus, this work aimed to analyze the variation in the energy balance on the surface in a farm area, natural field and forest for the region of Humaitá, AM, Brazil. The satellite data was collected in the years 2000, 2005, 2015 and 2020 and processed in geeSebal. The automatic calibration technique was performed to identify the hot and cold pixels. The energy balance variables were estimated using the simplified version of the Calibration Using Inverse Modeling at Extreme Conditions algorithm, developed for the METRIC model and applicable to the SEBAL algorithm. Statistical analysis was performed using descriptive statistics, using the Kruskal-Wallis test and Dunn’s post-hoc test. The results showed that soil heat flux and sensible heat flux were lower in forests and higher in fields and farms. The latent heat flux and net radiation assumed the highest values in forests and lowest in fields and farms. The post-hoc Dunn test showed a similarity between the fields and farm areas. Finally, the SEBAL model satisfactorily estimated the components of the energy balance at the surface, in addition to highlighting the increase in sensible heat and the decrease in latent heat for the study areas.